A Real-World Experience Comparison of Percutaneous and Open Femoral Exposure for Endovascular Abdominal Aortic Aneurysm Repair in a Tertiary Medical Center. (July 2017) - Mukherjee, Dipankar; Emery, Erica; Majeed, Rashad; Heshmati, Keyvan; Hashemi, Homayoun
Objective: To compare the outcomes of elective percutaneous endovascular aneurysm repair (PEVAR) versus surgical cutdown endovascular aneurysm repair (SEVAR) procedures performed at a tertiary medical center from 2012 to 2015. Methods: This is a unique study using procedure data from two vascular surgeons who performed SEVAR in almost every case versus three vascular surgeons who performed PEVAR in all cases except when considered prohibitive on account of circumferential calcification or severe occlusive disease of the common femoral artery or some other technical consideration. Medical records of patients aged 18 years or older undergoing elective PEVAR or SEVAR between January 2012 and December 2015 were reviewed. Differences in readmissions and complications between patients who received PEVAR and those who received SEVAR were assessed using Fisher's exact test. The exact Cochran-Armitage test was used to assess trends in length of stay between the PEVAR and SEVAR group. Results: A total of 183 patients were analyzed. In total, 132 underwent PEVAR and 51 underwent SEVAR. A statistically significant difference was noted with regard to 30-day readmissions (2.3% vs 13.7%, P = .006) in favor of PEVAR and categorical length of stay tended to be longer in the SEVAR group ( P = .003). The 30-day complication rate was not statistically different (6.8% vs 15.7%, P = .09). Conclusions: Surgical cutdown endovascular aneurysm repair results in more readmissions, often related to groin wound complications, which lead to prolonged length of stay and expense. Patients undergoing PEVAR tend to have a shorter length of stay. Overall complication rate was similar in the two groups. We recommend PEVAR for patients with appropriate anatomy.